2019
DOI: 10.21608/jappmu.2019.43003
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Discarded Dates as a Source of Energy in Silage Fermentation and the Effect of Silage Produced on the Performance of Dairy Cows

Abstract: This study was conducted to evaluate the effect of partial substitution of corn grain by discarded dates on silage quality and their effect on digestibility, milk production and composition. Sixteen crossbreed lactating Friesian cows were assigned to four balanced groups and fed individually for 90 days on experimental rations whereas: all the groups were received a basal diet with one of four kinds of silages as follows: 100 % crushed corn grain (T1), 75 % crushed corn grain + 25% discarded dates (T2), 50 % c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…El-Shora et al (2014) reported that lactating Friesian cows fed 33 and 66% DD had higher nutrient digestibility of all nutrients and nutritive values (TDN and DCP) compared to control groups (p<0.05). Also, Abo-Donia et al (2019) reported an insignificant increase in the digestibility of CP, CF, and fiber fractions in dairy cows fed DD in the silage at levels up to 75% replacing CG.…”
Section: Ration Composition Digestion Coefficients and Nutritive Valuesmentioning
confidence: 97%
See 4 more Smart Citations
“…El-Shora et al (2014) reported that lactating Friesian cows fed 33 and 66% DD had higher nutrient digestibility of all nutrients and nutritive values (TDN and DCP) compared to control groups (p<0.05). Also, Abo-Donia et al (2019) reported an insignificant increase in the digestibility of CP, CF, and fiber fractions in dairy cows fed DD in the silage at levels up to 75% replacing CG.…”
Section: Ration Composition Digestion Coefficients and Nutritive Valuesmentioning
confidence: 97%
“…The replacement of 0, 50, or 100% of corn grain in the diets of lactating Barki ewes with dates had no significant effect on milk production or composition (Khattab, 2013). Similarly, Abo-Donia et al (2019) reported that replacement of yellow corn grains in silage with discarded dates in crossing Friesian dairy cows' diets up to 75% had no significant impact on milk output and composition. However, Damani sheep fed 20 and 30% discarded dates on a dry matter (DM) basis produced more milk per day than those in control group.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations